(untitled) (Journal of Medicine, 2022)
Introduction: Robust data of CRP is available in bacterial infection, and now it can be utilized in Covid- 19 pneumonia pandemic initial assessment of severity and planning of treatment. Materials and Methods: Multicentric, prospective, observational and interventional study conducted during July 2020 to May 2021 included 1000 Covid-19 cases confirmed with RT PCR. All cases were assessed with lung involvement documented and categorized on HRCT thorax, oxygen saturation, inflammatory marker as CRP at entry point and follow up. Age, gender, Comorbidity and use BIPAP/NIV and outcome as with or without lung fibrosis as per CT severity were key observations. Statistical analysis is done by using Chi square test. Observations and analysis: Age (<50 and >50 years) and gender (male versus female) has significant association with CRP in predicting severity [p<0.00001] & [p<0.010] respectively. CT severity score at entry point with CRP level has significant correlation [p<0.00001] CRP level has significant association with duration of illness (Doi) [p<0.00001] Comorbidities has significant association with CRP level. [p<0.00001] CRP level has significant association with oxygen saturation [p<0.00001] BIPAP/NIV requirement during hospitalization has significant association with CRP level. [p<0.00001] Timing of BIPAP/NIV requirement has significant association with CRP level. [p<0.00001] Follow-up CRP titer during hospitalization as compared to entry point normal and abnormal CRP has significant association in post-covid lung fibrosis [p<0.00001] Conclusion: CRP is easily available and universally acceptable inflammatory marker in Covid-19 pandemic and ‘serial titer’ documented very crucial role in predicting severity of illness, need of ventilatory support and help in predicting post-covid lung fibrosis. J MEDICINE 2022; 23: 112-120